Antitumor activity in colorectal cancer induced by hinokiflavone. Issue 9 (16th January 2019) - Zhou, Jing; Zhao, Rongce; Ye, Tinghong; Yang, Shuping; Li, Yali; Yang, Fangfang; Wang, Gang; Xie, Yongmei; Li, Qiu
Abstract: Background and Aim: Colorectal cancer is one of the most common malignant disease worldwide with highly metastatic potential. Identification of effective therapeutic treatment overcoming such disease is an urgent need. Our study focuses on hinokiflavone as an antitumor agent against colorectal cancer. Methods: MTT assay, cell colony formation assay, Hoechst staining, flow cytometry, Western blot analysis, real‐time polymerase chain reaction, and migration and invasion assay were performed to identify the effects of hinokiflavone on cell proliferation, apoptosis, and metastasis. CT26 tumor‐bearing mice model was conducted to explore the antitumor activity of hinokiflavone in vivo . Immunohistochemistry staining was used to detect the protein expression of Ki‐67, cleaved caspase‐3, and MMP9 in treated tumors. Acute toxicity was evaluated by serological and hematological analyses, and drug side effect on organs was evaluated by hematoxylin and eosin staining. Results: Hinokiflavone reduced the proliferation, migration, and invasion and promoted the apoptosis in colorectal tumor cells in vitro . Treatment of hinokiflavone at a tolerable and safe dose (50 mg/kg) significantly suppressed tumor growth in mice bearing CT26 tumors by reducing tumor proliferation and metastasis and inducing apoptosis. Mechanically, treatment of hinokiflavone induced apoptosis by loss of mitochondrial transmembrane potential and increased reactive oxygen species generation. Conclusions: Hinokiflavone suppressed colorectal tumor cell proliferation, induced apoptosis via the reactive oxygen species–mitochondria‐mediated apoptotic pathway, and inhibited tumor cell migration and invasion. Antitumor activity of hinokiflavone was also validated in mice model without observed toxicity. Our findings suggested that the plant‐derived hinokiflavone could be used as an antitumor agent against colorectal cancer.